Transfer of Ownership in Sale Contracts Involving Carriage of Goods by Sea - al-Daboubi, Derar (2021)
This article discusses the maritime carrier’s effect on the transfer of ownership be tween contracting parties to international sales. The discussion initially focuses on the relevant provisions of the United Nations Convention on Contracts for the International Sale of Goods 1980 (CISG), and Incoterms 2010 Rules as international instruments. It will also cover the provisions of the Jordanian Civil Code 1976 (JCC) as a domestic statute. The necessity to examine the maritime carrier’s influence on transfer of ownership lies in the impact it can exert on a buyer’s right to acquire own ership that may deprive him of selling the goods in transit. This article will point out the obstacles encountered when determining the timing for transfer of ownership. The study proposes some suggestions through which the role the maritime carrier plays in the transfer of ownership can be recognized and the time when transfer of ownership occurs can be easily determined.